Facilitating interdisciplinary research (National Academies Press, 2005)
Examines current interdisciplinary research efforts and recommends ways to stimulate and support such research. Identifies steps that researchers, teachers, students, institutions, funding organizations, and disciplinary societies can take to more effectively conduct, facilitate, and evaluate interdisciplinary research programs and projects. Throughout the report key concepts are illustrated with case studies and results of the committee s surveys of individual researchers and university provosts.